Characteristics of CEO, Family Board Members and Internationalization of Family Companies Listed on the IDX - Rahmat Setiawan; Aditya Sahrul Bagaskara; Masfufah Masfufah (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this research is to examine the influence of the CEO Characteristics and family board member on a family firms internationalization listed on the Indonesia Stock Exchange. This research is using multiple linear regression model, the data is acquired from report finance company published from period 2011-2016. Dependent variables used is internationalization proxied with foreign sales to total sales. Independent variables in this research are education level of the CEO, Gender of the CEO, family board member of commissioner and family board member of director. The result of this research shows that the education level of the CEO has a positive effect on internationalization, the CEO's gender is not significant to internationalization, while the family board member of com-missioners and family board member of director are negatively afflicted against internationalization.